Kajian Pengembangan Budidaya Ikan Lele di Kota Kupang - Aris Widagdo; Dimas Rizky Hariyadi; I Made Aditya Nugraha; Ni Putu Dian Kusuma; Zainal Usman (Jurnal Inovasi Kebijakan, 2022)
Assistance in the form of seeds and feed will become one of the programs of the Kupang City Maritime Affairs and Fisheries Department in 2022 to improve the economy of 56 catfish farmers. The purpose of the study was to analyze the impact of capital, human resources, and marketing on yield in catfish farming. The investigation was conducted in the city of Kupang for 120 days. Data was collected through observations, questionnaires, and interviews and analyzed for rank spearman correlation, multiple regression, and SWOT analysis. Capital, human resources, and marketing factors significantly affected catfish production in Kupang City, with Rank Spearman's correlation p-value (0.024?0.050), p-value (0.021?0.050), and p-value (0.000?0.050). 0.277, 0.283, and 0.548 were obtained. The direction of the influence relationship of capital, human resources, and marketing factors on production is positive, meaning that production increases as capital increases, and production increases as capital increases. Better human resources capabilities lead to higher productivity and vice versa. Every time there is a change in production inputs, such as capital and human resources (labor), it affects the production at the catfish farm in Kupang City. Development strategies are implemented through consulting and training, expanded access to capital and large-scale promotions.